2020
DOI: 10.2215/cjn.08890719
|View full text |Cite
|
Sign up to set email alerts
|

Disease Modeling To Understand the Pathomechanisms of Human Genetic Kidney Disorders

Abstract: The class of human genetic kidney diseases is extremely broad and heterogeneous. Accordingly, the range of associated disease phenotypes is highly variable. Many children and adults affected by inherited kidney disease will progress to ESKD at some point in life. Extensive research has been performed on various different disease models to investigate the underlying causes of genetic kidney disease and to identify disease mechanisms that are amenable to therapy. We review some of the research highlights that, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 143 publications
0
13
0
Order By: Relevance
“…Several disease models (animal and cellular) for inherited kidney diseases have been developed to identify aberrant pathways and novel therapeutic targets, or as drug screening and testing platforms [ 4 ]. Deviating from animal models that are unable to fully recapitulate human pathophysiology, human models are becoming highly appealing [ 13 ].…”
Section: In Vitro Cell-based Models Of Genetic Kidney Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several disease models (animal and cellular) for inherited kidney diseases have been developed to identify aberrant pathways and novel therapeutic targets, or as drug screening and testing platforms [ 4 ]. Deviating from animal models that are unable to fully recapitulate human pathophysiology, human models are becoming highly appealing [ 13 ].…”
Section: In Vitro Cell-based Models Of Genetic Kidney Diseasesmentioning
confidence: 99%
“…A plethora of disease models, ranging from zebrafish and C. elegans to rodents and in vitro patient-derived cell culturing, have contributed to the identification of novel genetic causes, new therapeutic targets, and to the development of new treatments. For a better overview of these models, we guide the reader to the work of Molinari et al [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Eventually, regarding the genetically tractable characteristics of zebrafish, it can be developed into a transgenic model as one of the strategies of its application in personalized medicine in different fields of human diseases ( 3 , 63 , 69 ). Since many kidney diseases are caused by mono/polygenic mutations, zebrafish is used to both reveal the underlying genetic mutation and pathophysiology and model for drug screening in the hopes of personalized medicine) ( 71 73 ). On the other hand, zebrafish is distinctly useful in personalized medicine when treatment options are abundant, etiologies are not well-established, or the abnormality is rare; like endocrine disorders, cancers, and Duchene muscular dystrophy ( 11 , 74 , 75 ).…”
Section: Humanized Zebrafish Model For Personalized Regenerative Medimentioning
confidence: 99%
“…Caenorhabditis elegans , where cilia are found at the ends of the dendrites of 60 sensory neurons (Inglis et al, 2007) . Many ciliopathy proteins and associated pathways are conserved in the worm (Kim et al, 2018;van Dam et al, 2019) , and C. elegans studies have led to seminal discoveries that have greatly instructed our understanding of cilia biology in vertebrates and mammals (Blacque & Sanders, 2014;Ganner & Neumann-Haefelin, 2017;Mok & Héon, 2012;Molinari & Sayer, 2020) . Genetic studies in C. elegans have revealed that TZ proteins function within two distinct entities termed the 'NPHP' and 'MKS' modules (Williams et al, 2008(Williams et al, , 2011 .…”
Section: Tz Structure Function and Molecular Organisation Is Especiamentioning
confidence: 99%